1996
DOI: 10.1111/j.1528-1157.1996.tb01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Extratemporal Epilepsy: Clinical, Radiologic, and Histopathologic Findings in 60 Patients

Abstract: Focal lesions and particularly neoplasms are associated with improved postoperative seizure control compared with patients without histopathologic abnormalities. We advise caution in considering surgery to treat extratemporal epilepsy in patients who have normal MRI scans, because the outcome with the approach described in this study is poor in such cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
108
4
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(121 citation statements)
references
References 26 publications
(12 reference statements)
8
108
4
1
Order By: Relevance
“…Conversely, in cases of extra-TLE, the degree of clinical correlations was clearly better with MRI than EEG, and EEG-MRI correlation provided another basis for the syndromic diagnosis, also superior to the clinical-EEG correlation. Thus MRI seemed to be an invaluable addition to ICEES for the topographic diagnosis of extra-TLE, a finding in good agreement with the results of presurgical evaluations of intractable neocortical epilepsies (16,27,28). However, the topographic diagnosis of extra-TLE was still problematic, even with the incorporation of MRI, as evidenced by the absence of any concordance among the three correlations in 42% of patients and a <50% detection rate of lesions by MRI.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Conversely, in cases of extra-TLE, the degree of clinical correlations was clearly better with MRI than EEG, and EEG-MRI correlation provided another basis for the syndromic diagnosis, also superior to the clinical-EEG correlation. Thus MRI seemed to be an invaluable addition to ICEES for the topographic diagnosis of extra-TLE, a finding in good agreement with the results of presurgical evaluations of intractable neocortical epilepsies (16,27,28). However, the topographic diagnosis of extra-TLE was still problematic, even with the incorporation of MRI, as evidenced by the absence of any concordance among the three correlations in 42% of patients and a <50% detection rate of lesions by MRI.…”
Section: Discussionsupporting
confidence: 52%
“…Over the past decade, magnetic resonance imaging (MRI) has exerted a great impact on the practice of epilepsy management. MRI may detect lesions in 50% to 74% of patients with LE attending an epilepsy clinic (17,18), and the presence of lesions in MRI may provide reliable evidence of seizure origin as well as other important clinical information such as etiology, surgical accessibility and outcome, prognosis, or responses to drug therapy (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). However, no attempt to incorporate MRI features into the current ICEES has yet been systematically undertaken.…”
mentioning
confidence: 99%
“…The proportion of our patients without demonstrated specific lesions (10%) is lower than that in most epilepsy surgical series, possibly because of the strict inclusion criteria of our study and its more recent time span (3)(4)(5)(6)(7)(8)(9)(11)(12)(13)15,16,28,29). Eleven of these reports specifically described pathology; of these, the proportion of all patients with normal or nonspecific pathology ranged from 6 to 58% (median, 20%; average, 25%).…”
Section: Nonlesional Incidence In Surgical Seriesmentioning
confidence: 82%
“…Fourteen epilepsy surgery series (3-16) used MRI and/or histopathology to disclose specific lesions. Eight of these (3,4,6,(9)(10)(11)(12)15) agreed with Penfield (17,18) that the presence of a specific epileptogenic lesion usually augurs a favorable postsurgical outcome (Table 1). Additionally, Bengzon et al (19), compiling the Montreal experience, found a higher proportion of patients with lesions in the favorable-outcome group than among those in whom resective surgery was unhelpful.…”
mentioning
confidence: 83%
“…The resection of an epileptogenic lesion within an ictal onset zone (IOZ) is recognized as among the most important factors linked to a favorable surgical outcome [3]. The majority of surgical series have suggested that the presence of a specific lesion usually leads to a favorable surgical outcome [24]. The presence of a lesion increases the likelihood of seizure freedom and thus, brain MRI is relatively good at predicting the prognosis of neocortical epilepsy.…”
Section: Neuropathology In Neocortical Epilepsy: Does Nonlesional Neomentioning
confidence: 99%